2019
DOI: 10.7196/sajcc.2019.v35i1.388
|View full text |Cite
|
Sign up to set email alerts
|

Developing a theory of family care during critical illness

Abstract: Critical illness of a loved one and subsequent admission into the critical care unit (CCU) have notable effects on family members (FMs). Many studies have acknowledged the importance of identifying the needs of FMs during this difficult period in an attempt to ease the effects of this crisis. [1-4] Molter's seminal work [5] that explored the needs of FMs led to the development of the Critical Care Family Needs Inventory, which categorises family needs into five domains, namely assurance, proximity, comfort, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…Also, a study conducted in Ghana ( Ohene et al, 2017 ) among parents of road traffic accidents in the emergency unit reported that health workers supported family belief and inspired them to engage in prayers and rituals to support the medical care they are receiving. Beer and Brysiewicz (2019) in development of a theory to guide caring for family members when their loved ones are suffering from critical health conditions, emphasized the importance of the concept of religious and cultural collaboration in family care. According to health belief model, belief that people hold may influence behavior; perceived benefits of rituals/prayers may influence positive coping behavior of families ( Tsai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study conducted in Ghana ( Ohene et al, 2017 ) among parents of road traffic accidents in the emergency unit reported that health workers supported family belief and inspired them to engage in prayers and rituals to support the medical care they are receiving. Beer and Brysiewicz (2019) in development of a theory to guide caring for family members when their loved ones are suffering from critical health conditions, emphasized the importance of the concept of religious and cultural collaboration in family care. According to health belief model, belief that people hold may influence behavior; perceived benefits of rituals/prayers may influence positive coping behavior of families ( Tsai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The complete comprehension of the family about the patient's condition was also crucial to prevent the psychological problem, which could be achieved by involvement of the close family in their children nursing and good communication between health professionals and the family throughout and after the intensive care. [ 19 ] None of the internal and external risk factors evaluated in this study had a significant impact on the family psychological condition. It showed that clear continuous communication and the involvement of the family, as not evaluated in this study, were the key aspects to maintain the good psychological condition of the family.…”
Section: Discussionmentioning
confidence: 87%
“…Actividades para suplir la necesidad de proximidad: De acuerdo con De Beer 36 la proximidad se refiere a ser flexible con respecto al acceso de la familia al entorno del paciente y hacer que sea más fácil (tanto física como psicológicamente) el estar cerca de su ser querido; dicha cercanía le permite a los miembros de la familia monitorear la situación, rastrear la atención brindada y desarrollar confianza con el personal que brinda atención; esto también es acorde con lo encontrado por Shorofi et al 37 donde se encontró que la proximidad es una de las principales necesidades de la familia en la UCI adulto.…”
Section: Discussionunclassified